Observation and modeling of high-7Be events in Northern Europe associated with the instability of the Arctic polar vortex in early 2003 - Brattich, Erika; Liu, Hongyu; Zhang, Bo; Hernández-Ceballos, Miguel Ángel; Paatero, Jussi; Sarvan, Darko; Djurdjevic, Vladimir; Tositti, Laura; Ajtić, Jelena (2021)
Events of very high concentrations of 7 Be cosmogenic radionuclide have been recorded in the subpolar regions of Europe during the cold season. With an aim to investigate the mechanisms responsible for those peak 7 Be events, and in particular to verify if they are associated with the fast descent of stratospheric air masses occurring during sudden stratospheric warming (SSWs), we analyse 7 Be observations at six sampling sites in Scandinavia during January–March 2003 when very high 7 Be concentrations were observed and the Arctic vortex was relatively unstable as a consequence of several SSWs. We use the GEOS-Chem chemistry and transport model driven by the MERRA-2 meteorological reanalysis to simulate tropospheric 7 Be over Northern Europe. We show that the model reasonably reproduces the temporal evolution of surface 7 Be concentrations observed at the six sampling sites. Our analysis of model simulations, surface 7 Be observations, as well as atmospheric soundings of ozone and temperature indicates that the 7 Be peak observed in late February 2003 (between 20 and 28 February 2003) at the six sampling sites in Scandinavia was associated with downward transport of stratospheric vortex air originated during SSW that occurred a few days before the peak (18–21 February 2003).